Impact of foliar application of some metal nanoparticles on antioxidant system in oakleaf lettuce seedlings - Jurkow, Rita; Pokluda, Robert; Sękara, Agnieszka; Kalisz, Andrzej (BMC plant biology, 2020)
BACKGROUND: Nanoparticles (NPs) serve various industrial and household purposes, and their increasing use creates an environmental hazard because of their uncontrolled release into ecosystems. An important aspect of the risk assessment of NPs is to understand their interactions with plants. The aim of this study was to examine the effect of Au (10 and 20 ppm), Ag, and Pt (20 and 40 ppm) NPs on oakleaf lettuce, with particular emphasis on plant antioxidative mechanisms. Nanoparticles were applied once on the leaves of 2-week-old lettuce seedlings, after next week laboratory analyses were performed. RESULTS: The antioxidant potential of oakleaf lettuce seedlings sprayed with metal NPs at different concentrations was investigated. Chlorophylls, fresh and dry weight were also determined. Foliar exposure of the seedlings to metal NPs did not affect ascorbate peroxidase activity, total peroxidase activity increased after Au-NPs treatment, but decreased after applying Ag-NPs and Pt-NPs. Both concentrations of Au-NPs and Pt-NPs tested caused an increase in glutathione (GSH) content, while no NPs affected L-ascorbic acid content in the plants. Ag-NPs and Pt-NPs applied as 40 ppm solution increased total phenolics content by 17 and 15%, respectively, compared to the control. Carotenoids content increased when Ag-NPs and Au-NPs (20 and 40 ppm) and Pt-NPs (20 ppm) were applied. Plants treated with 40 ppm of Ag-NPs and Pt-NPs showed significantly higher total antioxidant capacity and higher concentration of chlorophyll a (only for Ag-NPs) than control. Pt-NPs applied as 40 ppm increased fresh weight and total dry weight of lettuce shoot. CONCLUSIONS: Results showed that the concentrations of NPs applied and various types of metal NPs had varying impact on the antioxidant status of oakleaf lettuce. Alteration of POX activity and in biosynthesis of glutathione, total phenolics, and carotenoids due to metal NPs showed that tested nanoparticles can act as stress stimuli. However, judging by the slight changes in chlorophyll concentrations and in the fresh and dry weight of the plants, and even based on the some increases in these traits after M-NPs treatment, the stress intensity was relatively low, and the plants were able to cope with its negative effects.
Keywords: Platinum; Plant Leaves; Lactuca; Chlorophyll; Silver; antioxidancia; salát (hlávkový); Gold; Metal Nanoparticles; Lactuca sativa L. var. foliosa; Antioxidants; Seedlings; Nanometals; kovové nanočástice; semenáček; listy rostlin